Hyperprolactinaemia associated with increased thyroid volume and autoimmune thyroiditis in patients with prolactinoma. (15th May 2013) - Sayki Arslan, Muyesser; Sahin, Mustafa; Topaloglu, Oya; Tutal, Esra; Karakose, Melia; Gungunes, Askin; Cakal, Erman; Ozbek, Mustafa; Delibasi, Tuncay
Summary: Objective: The aim of this investigation was to evaluate the effects of hyperprolactinaemia on thyroid function, volume and nodularity in patients with prolactinoma. Context: Hyperprolactinaemia has been associated with various autoimmune diseases; however, the data on the correlation between the level of prolactin (PRL) and thyroid disorders have not been adequately clarified. Design: Case–control study. Patients: Forty‐eight subjects with new diagnosis of hyperprolactinaemia (group 1) and 39 subjects undergoing treatment for prolactinoma (group 2) were recruited from our outpatient clinic. Fifty‐two healthy subjects were included as a control group (group 3). Measurements: The serum PRL, thyroid‐stimulating hormone (TSH), thyroxine (free T4), thyroidal microsome (anti‐TPO) and antithyroglobulin antibodies (TgAb) levels were evaluated, and ultrasonographic thyroid volume was calculated. Results: The frequencies of positive anti‐TPO and TgAb were significantly higher in group 1 than in groups 2 and 3 ( P  = 0·008). Also, the percentage of patients with thyroid heterogeneity were significantly higher in groups 1 and 2 than in group 3 ( P  < 0·05). The percentage of patients with thyroid nodules were higher in group 1 than in groups 2 and 3 (p1–2  = 0·03, p1–3  = 0·05 and p2–3  = 0·637). The mean thyroid volume was significantly higher in group 1 ( P  = 0·001), and a positive correlation was found between thyroid volume and the level of PRL ( r  = 0·616; P  = 0·0001). Prolactin had a significant effect on the total volume according to stepwise multiple linear regression analysis (adjusted R 2 is 0·268; P  < 0·0001). Conclusions: Patients with hyperprolactinaemia have significantly increased thyroid volume, thyroid autoimmunity and nodule prevalence.